The marketing logistics in the management system of the enterprise - Нurzhii Nataliia; Shyshkin, Viktor; Kravchenko, Anastasiia (Management and Entrepreneurship: Trends of Development, 2018)
Taking into account today’s state of the market environment and the requirements for the modern enterprises, there is one of the most important tasks – to find new solutions in the field of the marketing and logistics and combine their autonomous functions into a single system. By its nature the marketing logistics is the system of the planning, operational management and control of material flows, that aims to meet consumers’ inquiries in the most effective way. The marketing logistics is based on the integration of the marketing and logistics ideas. Here the tasks of the manufacturing assortment loading, based on the stock of orders formed by the marketing services, are solved, the optimal resource transfer technology is determined, the requirements for the products quality are developed, the loss centers are defined etc. Thus the main task of the marketing logistics is to manage the flow of finished products, proceeding in the direction from the manufacturer to the consumer. Purpose. The subject of the study is the economic relations developed in the process of the implementation of the marketing logistics at the enterprise. The purpose of the paper is to determine the features of the marketing logistics in the management system of the enterprise. Design/methodology/approach. The basic principles of this research are the causality and objectivity principles, systematic and comparative methods, institutional and structural-functional approach. Findings. In this article the features of the marketing logistics are described. Also the ways of the possible problems solving are suggested. According to the done research, the marketing logistics is characterized by the following. • The marketing logistics heads for the optimization of the commodity circulation on the basis of the market orientation and the economic flows optimization. • The marketing logistics forms the product demand actively due to the implementation of the marketing measures and the development of the logistics service system as well. • The marketing logistics furthers the object transformation of the target market and the economic flow in logistics into an integrated commodity circulation as the main object of the marketing and logistics efforts. • The marketing logistics has the combined type of the management, which combines the market-oriented manufacturing and the economic flows organization at the enterprise. Thus, the concept of the marketing logistics is a system of views on the meeting consumers needs in order to achieve sustainable competitive advantages by improving the economic activity efficiency through economic flows optimization. It is implemented on the systematic approach basis to the use of the marketing and logistics in the business and involves the active use of the modern information technologies. Research limitations/implications. The scientific significance of the article consists in the research of the possible ways of the marketing logistics implementation, based on its features, at the domestic enterprises. Originality/value. The described in this article features of the marketing logistics implementation and the ways of the possible problems solving will further the increase of the Ukrainian enterprises’ competitiveness and will multiply their financial results. The marketing logistics considering as the basic element of the competitive strategy and its implementation will secure the uninterrupted, mutually agreed and effective activity of the enterprises